2009
DOI: 10.1007/s10067-009-1149-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of tumor necrosis factor-α (TNF-α) antagonists infliximab, etanercept, and adalimumab in patients with concurrent rheumatoid arthritis and hepatitis B or hepatitis C: a retrospective record review of 11 patients

Abstract: An understanding of the cytokine cascade in a rheumatoid joint has led to the development of new therapeutic options, including drugs targeting tumor necrosis factor-alpha (TNF-alpha). The safety profile of these agents in patients with hepatitis-induced liver disease, however, remains a concern because of risks associated with immune suppression. To examine the effect of three different TNF-alpha antagonists, infliximab, etanercept, and adalimumab, on serum transaminases and hepatitis viral load in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 12 publications
0
54
0
5
Order By: Relevance
“…Overall, most published reports indicate that anti-TNF agents are safe in patients infected with hepatitis C, 19,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] as recently reviewed. 1 However, the safety of anti-TNF agents in patients with advanced HCV-related fibrosis is unknown.…”
Section: Impact Of Anti-tnf Therapy In Patients With Underlying Chronmentioning
confidence: 99%
“…Overall, most published reports indicate that anti-TNF agents are safe in patients infected with hepatitis C, 19,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] as recently reviewed. 1 However, the safety of anti-TNF agents in patients with advanced HCV-related fibrosis is unknown.…”
Section: Impact Of Anti-tnf Therapy In Patients With Underlying Chronmentioning
confidence: 99%
“…A recent retrospective study showed 1 case of viral reactivation among 8 HBsAg carriers treated with anti-TNF␣ therapy (24). On the other hand, many cases have been described in which TNF blockade, either in association with lamivudine prophylactic therapy or not, did not lead to HBV reactivation (6,(25)(26)(27)(28)(29)(30), and recently a retrospective study showed no reactivation during anti-TNF␣ therapy (31). The use of lamivudine to prevent HBV reactivation is recommended in HBsAg-positive patients undergoing immunosuppressive therapies, including anti-TNF␣ drugs (4,32), but its use can lead to viral resistance (33).…”
Section: Introductionmentioning
confidence: 99%
“…However, in clinical practice, it is necessary to use anti-TNF-a in these patients. Table 1 summarizes the course of nine patients who received etanercept according to our literature search [16,[22][23][24][25][26]. Nine of four patients were women.…”
Section: Discussionmentioning
confidence: 99%